Improving access to oral health care for vulnerable and underserved populations (National Academies Press, 2011)
"Access to oral health care is essential to promoting and maintaining overall health and well-being yet only half of the population visits a dentist each year. Poor and minority children are less likely to have access to oral health care than are their nonpoor and nonminority peers. Older adults, people who live in rural areas, and disabled individuals, uniformly confront access barriers, regardless of their financial resources. The consequences of these disparities in access to oral health care can lead to a number of conditions including malnutrition, childhood speech problems, infections, diabetes, heart disease, and premature births. Improving access to oral health care for vulnerable and underserved populations examines the scope and consequences of inadequate access to oral health services in the United States and recommends ways to combat the economic, structural, geographic, and cultural factors that prevent access to regular, quality care. The report suggests changing funding and reimbursement for dental care; expanding the oral health work force by training doctors, nurses, and other nondental professionals to recognize risk for oral diseases; and revamping regulatory, educational, and administrative practices. It also recommends changes to incorporate oral health care into overall health care. These recommendations support the creation of a diverse workforce that is competent, compensated, and authorized to serve vulnerable and underserved populations across the life cycle. The recommendations provided in Improving access to oral health care for vulnerable and underserved populations will help direct the efforts of federal, state, and local government agencies; policy makers; health professionals in all fields; private and public health organizations; licensing and accreditation bodies; educational institutions; health care researchers; and philanthropic and advocacy organizations."--Publisher's description.